Photocurrent Extraction Efficiency near Unity in a Thick Polymer Bulk Heterojunction. (22nd February 2016) - Ko, Seo‐Jin; Walker, Bright; Nguyen, Thanh Luan; Choi, Hyosung; Seifter, Jason; Uddin, Mohammad Afsar; Kim, Taehyo; Kim, Seongbeom; Heo, Jungwoo; Kim, Gi‐Hwan; Cho, Shinuk; Heeger, Alan J.; et al.
Abstract : The detailed characterization of a dialkoxyphenylene‐difluorobenzothiadiazole based conjugated polymer poly[(2, 5‐bis(2‐hexyldecyloxy)phenylene)‐alt‐(5, 6‐difluoro‐4, 7‐di(thiophen‐2‐yl)benzo[c][1, 2, 5]thiadiazole)] (PPDT2FBT) is reported. PPDT2FBT closely tracks theoretical photocurrent production while maintaining a high fill factor in remarkably thick films. In order to understand the properties that enable PPDT2FBT to function with thick active layers, the effect of film thickness on the material properties and device parameters was carefully studied and compared to three benchmark polymers. Optical modeling, grazing incidence wide angle X‐ray scattering, cross‐sectional transmission electron microscopy, transient photoconductivity, and extensive device work were carried out and have clarified the key structural features and properties that allow such thick active layers to function efficiently. The unique behavior of thick PPDT2FBT films arises from high vertical carrier mobility, an isotropic morphology with strong, vertical π–π stacking, and a suitable energy band structure. These physical characteristics allow efficient photocurrent extraction, internal quantum efficiencies near 100% and power conversion efficiencies over 9% from exceptionally thick active layers in both conventional and inverted architectures. The ability of PPDT2FBT to function efficiently in thick cells allows devices to fully attenuate incident sunlight while providing a pathway to defect‐free film processing over large areas, constituting a major advancement toward commercially viable organic solar cells. Abstract : A unique conjugated polymer (PPDT2FBT) is found to closely track theoretical photocurrent production and maintain a high fill factor in remarkably thick films. The unique behavior of thick PPDT2FBT films arises from high vertical carrier mobility and a morphology with strong, vertical π–π stacking, allowing efficient photocurrent extraction and internal quantum efficiencies near 100% from exceptionally thick active layers.